Data-driven discovery of Green's functions - Boullé, N (2022)
Discovering hidden partial differential equations (PDEs) and operators from data is an important topic at the frontier between machine learning and numerical analysis. Theoretical results and deep learning algorithms are introduced to learn Green's functions associated with linear partial differential equations and rigorously justify PDE learning techniques.